2015
DOI: 10.4172/2167-0420.1000284
|View full text |Cite
|
Sign up to set email alerts
|

Risky Sexual Behaviors for HIV Infection among Female Private College Students in Nekemte Town, Western Ethiopia

Abstract: Background: HIV/AIDS risky behavior remains a critical health concern for young women for multiple biological and socio-economic reasons. Hence, the objective of the study was to assess the level of risky sexual behaviors and associated factors among female students in private colleges in Nekemte town, western Ethiopia. Methods:A cross-sectional study was carried out among female private college students in Nekemte town between April and May, 2014. A total of 422 female students in private colleges were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…However, this study is lower when compared to the study done on the premarital sexual debut of the female school students in Bahir Dar town, Ethiopia; risky sexual practice and associated factors among secondary and preparatory school students of Aksum town, northern Ethiopia, 2018, and in Nekemte town among private college students showed that respondents who viewed sexual films were 4.9, 10.2, and 10.7 times more likely to practice risky sexual behavior respectively. 2830 This variation may be owing to the differences in place of residence and accessibility of the Internet and sophisticated mobile phone around urban areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study is lower when compared to the study done on the premarital sexual debut of the female school students in Bahir Dar town, Ethiopia; risky sexual practice and associated factors among secondary and preparatory school students of Aksum town, northern Ethiopia, 2018, and in Nekemte town among private college students showed that respondents who viewed sexual films were 4.9, 10.2, and 10.7 times more likely to practice risky sexual behavior respectively. 2830 This variation may be owing to the differences in place of residence and accessibility of the Internet and sophisticated mobile phone around urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…This result is higher compared to the study conducted among private college students in Nekemte Town in which unmarried students were nearly 3 times more likely to have multiple sexual partners than married. 29 This difference might be that individuals separated from their parents start to practice risky sexual behaviors because they are out of control.…”
Section: Discussionmentioning
confidence: 99%
“…To improve validity, a standardized questionnaire on "Asking young people about sexual and reproductive behaviour" by [19,24] was adopted. The standardised tool also improved reliability.…”
Section: Reliability and Validitymentioning
confidence: 99%
“…Several factors such as income deficit, Pre-college residence, pornographic film viewing and believe in sexual abstinence for HIV prevention were found to be significant predictors of initiating premarital sex. Younger generations could be advised to maintain the virginity as cultural norm and use of condom during sex before marriage is to be suggested [17]. Incorporation of sociostructural elements and geospatial techniques in analytical approaches would lead to better understanding of local dynamics and develop mediations that increase our facility of targeted HIV prevention services [18].…”
Section: Introductionmentioning
confidence: 99%